Strategi Penanganan Abrasi Berbasis Analisis Spasial di Pesisir Pantai Kecamatan Wonomulyo, Kabupaten Polewali Mandar - Asri, Haryanto; Jarir, Dewi Virgiastuti; Kamaruddin, Kamaruddin; Irna, Irna (Fakultas Kelautan dan Teknologi Perikanan - Universitas Negeri Gorontalo, 2025)
This study aims to analyze the rate of coastal abrasion and to formulate management strategies based on spatial and participatory approaches along the coastline of Wonomulyo District. The methods used include spatial analysis of shoreline changes from 2015 to 2025, field observations, and a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis to develop adaptive and context-specific strategies. The mapping results reveal that a significant portion of the coastline has experienced considerable abrasion, particularly in zones 84 to 86, where the shoreline has shifted most drastically inland. The novelty of this research lies in the integration of spatial abrasion data as a primary foundation for constructing practical management strategies. Unlike previous studies that primarily focused on mapping and identifying vulnerable zones, this research advances a zoning-based approach that incorporates technical, ecological, and social considerations. Four main strategies are proposed: (1) ecosystem-based restoration of coastal vegetation; (2) reinforcement of physical structures collaboratively designed and maintained with local communities; (3) enhancement of community capacity through training and assistance; and (4) institutional collaboration among government bodies, academics, and local conservation groups. The study concludes that effective abrasion management requires an integrated and participatory approach. Key recommendations include the need for regular mapping, strengthening of local capacities, and inter-institutional synergy in efforts to mitigate coastal abrasion.